3-Vinylazetidin-2-Ones: Synthesis, Antiproliferative and Tubulin Destabilizing Activity in MCF-7 and MDA-MB-231 Breast Cancer Cells - Shu Wang; Azizah M. Malebari; Thomas F. Greene; Niamh M. O'Boyle; Darren Fayne; Seema M. Nathwani; Brendan Twamley; Thomas McCabe; Niall O. Keely; Daniela M. Zisterer; Mary J. Meegan (MDPI AG, 2019)
Microtubule-targeted drugs are essential chemotherapeutic agents for various types of cancer. A series of 3-vinyl-β-lactams (2-azetidinones) were designed, synthesized and evaluated as potential tubulin polymerization inhibitors, and for their antiproliferative effects in breast cancer cells. These compounds showed potent activity in MCF-7 breast cancer cells with an IC50 value of 8 nM for compound 7s 4-[3-Hydroxy-4-methoxyphenyl]-1-(3,4,5-trimethoxyphenyl)-3-vinylazetidin-2-one) which was comparable to the activity of Combretastatin A-4. Compound 7s had minimal cytotoxicity against both non-tumorigenic HEK-293T cells and murine mammary epithelial cells. The compounds inhibited the polymerisation of tubulin in vitro with an 8.7-fold reduction in tubulin polymerization at 10 μM for compound 7s and were shown to interact at the colchicine-binding site on tubulin, resulting in significant G2/M phase cell cycle arrest. Immunofluorescence staining of MCF-7 cells confirmed that β-lactam 7s is targeting tubulin and resulted in mitotic catastrophe. A docking simulation indicated potential binding conformations for the 3-vinyl-β-lactam 7s in the colchicine domain of tubulin. These compounds are promising candidates for development as antiproiferative microtubule-disrupting agents.